Oral and maxillofacial surgical services amid COVID-19 pandemic: perspective from Tanzania - Karpal Singh Sohal; Elison N. M. Simon; Boniphace Kalyanyama; Jeremiah Robert Moshy (Tropical Medicine and Health, 2020)
Abstract The coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 is a global pandemic that affects individuals from all walks of life. Considering that the virus can be passed on directly from person to person through respiratory droplets, contact, fomites, and saliva, the oral and maxillofacial surgeons are exposed to COVID-19 in their daily clinical duties. This is because of the nature of their work, which entails working within a short distance from patients’ oral cavity and upper airway. As such, there is a need for having locally tailored standard guidelines for managing patients with oral and maxillofacial conditions during the COVID 19 pandemic in Tanzania.